Intensity Of Violent Behavior In Adolescents Addicted To Violent Online Games In Yogyakarta Indonesia - Fahrizal, Yanuar; Pratama, Bima Yoga (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2021)
The Online game is a technological product that is quite popular among adolescents. Violent characters in onlinegames can affect the game players. Hurting the enemies in the games every day will gradually lead adolescentsto think that hurting people is a fun and common thing to do. The adolescent delinquency cases in Yogyakartaoccur every year, and the most frequent cases are klitih (maltreatment) and brawls. This study aims to discoverthe relationship between the level of addiction to violent online games and the intensity of violent behavior inadolescents. This study employed a quantitative method with a cross-sectional approach. Data were collectedthrough Game Addiction Scale for Adolescent questionnaires by about the adolescents’ addiction to online gamesand violent behavior in adolescents. The respondents of the study were 96 adolescents, recruited using theLemeshow formula. Data were analyzed using the Spearmen rho test. Results showed that 48 adolescents (50%)were addicted to online games at a moderate level. The majority of adolescents (44.8%) had a low intensity ofviolent behavior. The p-value was 0.000 (<0.005). The correlation value was 0.731, indicating a strong correlationbetween online gaming addiction and intensity of violent behavior, and the positive value suggests aunidirectional relationship. The level of online gaming addiction in adolescents in Yogyakarta is moderate. Onlinegaming addiction and violent behavior have a significant relationship with a strong correlation coefficient and aunidirectional relationship. Future researchers are suggested to add research variables to discover other factors